Efeito das botas de compressão pneumática sobre a recuperação muscular após o exercício: revisão sistemática - Carvalho, Leandro Silva de (2021)
Background: Athletes commonly employ some strategies after exercise to accelerate the muscle recovery process. One of the most popular recovery tools is pneumatic compression boots. However, there is no consensus regarding the effectiveness of this resource for muscle recovery. Objective: To verify the effectiveness of using pneumatic compression boots after exercise, compared to any control or sham, on the decrease in DOMS, muscle fatigue, creatine kinase and blood lactate concentration, at any point in time. Methods: Searches were performed in electronic databases: Medline, EMBASE, CINAHL, CENTRAL, SPORTDiscus, LILACS, PEDro and SCIELO. The methodological quality of eligible studies was assessed using the PEDro scale. The risk of bias was assessed using the Cochrane ROB 2. All data included in the meta-analysis were analyzed in the “random effect” model. The overall quality of evidence was assessed by GRADE. Results: After the selection process, 6 studies were included in the meta-analysis. Compression boots were superior to passive rest for immediate muscle pain relief. However, it was not superior to massage, passive rest, or sham for improve fatigue and for decreasing blood lactate concentration. Conclusion: There is low quality of evidence that pneumatic compression boots are more effective than rest for decreasing muscle pain, immediately after the intervention, in ultramarathoners.